2017
DOI: 10.5114/ms.2017.66959
|View full text |Cite
|
Sign up to set email alerts
|

The management of patients with cardiogenic shock

Abstract: Cardiogenic shock is a life-threatening condition with a very poor prognosis. Many disorders may contribute to the development of shock. Of them, acute myocardial infarction is the main culprit. Despite tremendous progress in the field of interventional cardiology, in-hospital and long-term mortality still exceeds 50%. Data from large controlled trials on cardiogenic shock are scarce due to ethical reasons. Nevertheless, there is a chance for acceptable long-term survival in patients treated aggressively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Our study confirmed again that short-and longterm outcomes in patients with acute myocardial infarction are highly dependent on initial circulatory status (e.g. Killip scale) [13] as well as comorbidities (Table 3).…”
Section: Discussionsupporting
confidence: 83%
“…Our study confirmed again that short-and longterm outcomes in patients with acute myocardial infarction are highly dependent on initial circulatory status (e.g. Killip scale) [13] as well as comorbidities (Table 3).…”
Section: Discussionsupporting
confidence: 83%
“…Although previous studies indicate that females after pPCI have more bleeding complications compared to men [22, 23], we did not observe such dependence after adjustment for age. Surprisingly, some complications in the studied group occurred less frequently than in the whole population of patients with STEMI, applying to FWR or VSD [24].…”
Section: Discussionmentioning
confidence: 99%
“…In general, metabolic syndrome (MetS) is defined as a collection of multiple risk factors including abdominal obesity, dyslipidaemia, abnormal glycaemia, and elevated blood pressure [1]. Metabolic syndrome is also associated with an increased risk of type 2 diabetes, cardiovascular morbidity, and mortality [2][3][4][5][6][7]. Furthermore, there is an association between MetS and increased total cancer mortality [8,9].…”
Section: Introductionmentioning
confidence: 99%